Site-specific recombination - Grainge, I; Sherratt, D (2007)
Site-specific recombination is a reaction in which a pair of genetically defined sites undergoes reciprocal exchange ("crossing-over") via a recombinase-mediated DNA breakage and joining process. Such reactions have a wide range of biological outcomes, from integration and excision of virus genomes into and out of host chromosomes, to acquisition of novel genes and drug resistance, and even facilitating bacterial chromosome segregation. Two distinct families of recombinases exist, designated by their active site residues. In both these families recombination is carried out by a core of four recombinase monomers acting at two synapsed DNA sites. In many cases additional recombinase monomers and/or accessory proteins act at adjacent DNA sites to facilitate synapsis and often play a critical role in determining reaction topology. Here, the mechanism of site-specific recombination reactions is examined for both site-specific recombinase families, as well as for related proteins that mediate variant reactions, such as integrons and the integrases of conjugative transposons. © 2006 Springer-Verlag Berlin Heidelberg.